Does history repeat itself? Economic development and policy convergence in Vietnam and South Korea. (21st October 2019) - Turner, Mark; Jang, Hae‐Young; Kwon, Seung‐Ho; O'Donnell, Michael
Abstract : With one of the world's fastest rates of economic growth since the 1990s, Vietnam could be seen as Asia's next tiger economy. This study examines whether there has been policy convergence between the older East Asian developmental state model of economic development and that adopted by Vietnam. The economic development trajectories of South Korea and Vietnam are compared to identify similarities and differences. It was found that while policy convergence is evident there is also some divergence between the two countries.